Effectiveness of Police in Criminal Law Enforcement in the Digital Era from Islamic Legal Perspective : A Case Study of the Jambi Regional Police, Indonesia - Taufik Nurmandia; Risnita Risnita; Yuliatin Yuliatin; Abdul Halim (International Journal of Sociology and Law, 2026)
This study examines the effectiveness of the Jambi Regional Police in enforcing criminal law in the digital era, particularly in addressing online gambling offences, from the perspective of Islamic law. The rapid development of information technology has transformed crime from physical spaces into cyberspace, characterised by anonymity, speed, and transnational reach, thereby requiring adaptive law enforcement strategies. This research adopts a qualitative juridical-empirical approach. Data were collected through in-depth interviews with law enforcement officers at the Jambi Regional Police, analysis of case documents, and examination of relevant legal frameworks, particularly Indonesia’s Electronic Information and Transactions Law (ITE Law). The findings reveal that the Jambi Regional Police have implemented several strategic measures in combating digital crimes, including cyber patrols, digital forensic investigations, seizure of electronic evidence, and inter-agency coordination. Nevertheless, the effectiveness of law enforcement remains constrained by technological limitations, complex digital evidence requirements, the transnational nature of cybercrime, and limited public digital legal awareness. From an Islamic law perspective, police actions against online gambling align with the objectives of maqāṣid al-sharī‘ah, particularly the protection of religion (ḥifẓ al-dīn), property (ḥifẓ al-māl), and intellect (ḥifẓ al-‘aql). This study concludes that while digital criminal law enforcement by the Jambi Regional Police is fundamentally appropriate, it requires strengthened institutional capacity, integration of Islamic legal values, and adaptive policy reforms to enhance effectiveness and substantive justice.